The End Justifies the Means? The Impact of the ECB’s Unconventional Monetary Policy on Citizens’ Trust - Moritz Rehm; Martin Ulrich (Politics and Governance)
Since 2010, the European Central Bank (ECB) has established a range of unconventional monetary policies in the context of several crises, including cheap and long-term refinancing operations and several forms of asset purchases. This ECB action has been legally and politically challenged, raising the question as to how the public has perceived the ECB’s mandate widening. This article assesses the legitimacy of the ECB’s unconventional monetary policy through the lens of public trust using Eurobarometer data from 1999 to 2023. This approach follows the theoretical argument that the legitimacy of non-elected independent public institutions derives from the citizens’ trust in the fulfilment of the institutions’ tasks. Through panel regression analysis, this article first finds that trust in the ECB is commonly pooled with trust in other EU institutions, which makes a singular assessment of public support of the ECB and its policies difficult. Second, macroeconomic factors, which are partially influenced by ECB policies, but which are mostly dependent on national decision-making, are the key factors influencing citizens’ trust in EU institutions, including the ECB. Thus, citizens’ trust in the ECB or the lack thereof is not determined by the ECB’s use of contested unconventional monetary policy, but rather by the macroeconomic performance of their respective national economy.